The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5539/ijef.v8n10p82
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Global Financial Crisis, Does It Sustain?

Abstract: This paper studies the short and long term relationship between S&P500 USA stock market index and the stock market indices of 30 countries around the world over the period June 2010-April 2015. We implement OLS regression and use error correction model to examine the short and long term relationship between the variables. Empirically, we find that there is a relationship on the short and long term between S&P500 and the indices of 27 countries from East Asia, Europe, Latin America, Middle East as well as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The systematic observation of daily closing value of series based data analysis portrays the performance of the individual performances and the mutual dependency of one series on another at BSE. Granger causality test reveals unidirectional and in some case bidirectional causality in selected indices of BSE [1,3,27]. Further, Johansen Co-integration test clearly shows that there is a long run co-movement among selected series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic observation of daily closing value of series based data analysis portrays the performance of the individual performances and the mutual dependency of one series on another at BSE. Granger causality test reveals unidirectional and in some case bidirectional causality in selected indices of BSE [1,3,27]. Further, Johansen Co-integration test clearly shows that there is a long run co-movement among selected series.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Zu'bi et al studied the patterns of the stock price movement of various national and international stock exchanges and found that the price movements were very close during the subprime crisis. Moreover, volatility persists in every market [1].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Manifestly this observation was particularly witnessed during the recent Global Financial Crisis in 2008. When the USA faced the crisis, contagion captures other countries as reported by Al-Zu'bi et al (2016). These waves of global asset price movements have been further enthused by the improved cooperation of heightened cross-border capital flows, transparency of transactions via advance technology, the ease of capital mobility regulations, as well as added competitive market pressure on corporations to seek capital in the oversee within a climate of increasing overseas' investment options (Budd, 2014).…”
Section: Introductionmentioning
confidence: 99%